2021
DOI: 10.3390/nano11010227
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Signal Enhancement in Antibody Microarrays Using Lightguiding Nanowires

Abstract: Fluorescence-based detection assays play an essential role in the life sciences and medicine. To offer better detection sensitivity and lower limits of detection (LOD), there is a growing need for novel platforms with an improved readout capacity. In this context, substrates containing semiconductor nanowires may offer significant advantages, due to their proven light-emission enhancing, waveguiding properties, and increased surface area. To demonstrate and evaluate the potential of such nanowires in the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 46 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…Based on optics modeling for optimal lightguiding, the nanowire platforms were designed with the aim to display arrays of vertical nanowires with a diameter of ∼110 nm, expected to provide good lightguiding at the chosen fluorophore wavelength, 29 and with a spacing of 1 μm or more, sufficient to avoid optical nanowire–nanowire overlap at the illumination wavelength of 650 nm, 26 enabling single-nanowire analysis. In addition, for biomolecular functionalization purposes, the nanowires were modified with a SiO 2 coating of thickness t c .…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on optics modeling for optimal lightguiding, the nanowire platforms were designed with the aim to display arrays of vertical nanowires with a diameter of ∼110 nm, expected to provide good lightguiding at the chosen fluorophore wavelength, 29 and with a spacing of 1 μm or more, sufficient to avoid optical nanowire–nanowire overlap at the illumination wavelength of 650 nm, 26 enabling single-nanowire analysis. In addition, for biomolecular functionalization purposes, the nanowires were modified with a SiO 2 coating of thickness t c .…”
Section: Experimental Sectionmentioning
confidence: 99%
“… 29 Previous studies demonstrated the applicability of GaP nanowire arrays in single-molecule detection to study the diffusivity and concentration of membrane-bound proteins, 27 and they have been used for the detection of protein biomarkers, providing a 20-fold increase on sensitivity in contrast to conventional flat sensing surfaces. 26 In addition, vertically oriented GaP nanowires can be synthesized on GaP substrates by metal–organic vapor phase epitaxy (MOVPE), a nanoparticle-seeded, vapor–liquid–solid process that allows for optimization of fluorescence enhancement with much higher control over morphology, orientation, and positioning, as compared to solution-based methods used for instance for ZnO nanowires. However, MOVPE of GaP nanowires is not easily compatible with large-scale biosensing applications, for example, point-of-care diagnostics, because nanowire growth is a slow process and requires expensive GaP wafer substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of a fluorescence-based assay, Verardo et al developed a single chain fragment variable (scFv) antibody-based microarray platform consisting of SiO 2 -coated GaP nanowires [ 27 ]. Protein markers such as CEACAM-1, IL-5, and MCP-1were measured.…”
Section: Assay Miniaturizationmentioning
confidence: 99%
“…For example, for the MCP-1 protein, a concentration on the order of 100 pg/mL was found in serum, while for IL-5 it was on the order of 10 pg/mL. The prospect of a LOD below 1 pg/mL (i.e., ~10–100 fM) raised the sensitivity by 20-fold compared to conventional ELISA, making it a state-of-the-art immunoassay [ 27 ]. This method however did require additional steps and reagents to synthesize the nanowires and the array, making it inconvenient and less economical to use for wider applications.…”
Section: Assay Miniaturizationmentioning
confidence: 99%
See 1 more Smart Citation